1995
DOI: 10.1093/bja/74.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Normal postoperative gastric emptying after orthopaedic surgery with spinal anaesthesia and i.m. ketorolac as the first postoperative analgesic

Abstract: We have assessed the effect of i.m. ketorolac or morphine on early postoperative gastric emptying of liquids in patients undergoing orthopaedic surgery with spinal anaesthesia. Liquid gastric emptying was measured by absorption of paracetamol with patients acting as their own controls. There was no delay after ketorolac 30 mg, but morphine 10 mg resulted in marked delay. There was no difference in postoperative visual analogue pain scores between treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The absence of a delaying effect on upper g.i. Postoperative analgesia with intramuscular morphine significantly slowed gastric emptying and delayed resolution of postoperative ileus by impairing colonic motility compared with ketorolac in two separate studies [34,351. This is in contrast to morphine, which has several antipropulsive effects in the upper and lower g.i.…”
Section: Discussionmentioning
confidence: 98%
“…The absence of a delaying effect on upper g.i. Postoperative analgesia with intramuscular morphine significantly slowed gastric emptying and delayed resolution of postoperative ileus by impairing colonic motility compared with ketorolac in two separate studies [34,351. This is in contrast to morphine, which has several antipropulsive effects in the upper and lower g.i.…”
Section: Discussionmentioning
confidence: 98%
“…While surgical intervention itself is well understood to cause decreased gastrointestinal motility and delayed gastric emptying, it has been shown that opioid analgesics, 32–34 the fasting state, 35 and supine positioning 36 all independently contribute to delayed gastric emptying. In a recent United Kingdom study 7 comparing preoperative IV or PO acetaminophen 1,000 mg given preoperatively to patients undergoing surgery produced significantly different postoperative PK results, where the PO group experienced inadequate plasma levels for producing an effective pain response as compared to the therapeutic levels seen in the IV group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in many contexts including healthy volunteers [8,9], cardiac patients [11], patients with severe burns [12], and head injury [13], and in other anaesthetic related studies [14][15][16][17]. The paracetamol absorption test is based upon pharmacokinetic evidence [8] that paracetamol is not absorbed in the stomach but is rapidly absorbed from the small intestine after passage through the pylorus.…”
Section: Discussionmentioning
confidence: 99%